Chelba-Tutitti : site à stèles phalliques du sud de l’Éthiopie - Roger Joussaume (OpenEdition, 2010)
Many stelae were erected in the Rift Valley area in southern Ethiopia, some of which have been excavated since the early twentieth century, mostly by French teams. If the funeral nature of these standing stones – that are often decorated – has already been stressed for several of them (especially the swords’ stelae from Soddo and the anthropomorphic ones from the Gedeo country), nothing was really known about the thousands of phallic stelae from the Sidamo area. In 2009, a research programm devoted to these particular stelae started at the site of Chelbi-Tutitti, which yields a thousand standing stones. The first results, presented here, show that such stelae are not directly associated with graves, but could be related to a long barrow located north of the site, that will be the focus the field season, in December 2010. In 1925, F. Azaïs (1931) had already excavated a barrow associated with phallic stelae where he had found some human bones, a polished axe and many small obsidian objects, without understanding its relationship with the standing stones.